Business guide to trade remedies in Canada : anti-dumping, countervailing and safeguards legislation, practices and procedures (ITC GenevaCH, 2006)
Highlights those aspects of the law and practice of Canada and the appropriate provisions of the relevant WTO Agreements, which may be of practical interest to business managers, exporters and importers in developing countries and transition economies.
Keywords: DUMPING